Graffiti: ways to demarcate the city and redesign the landscape - Gandini, Marcelo Mattos; Bernardina, Jovani Dala (Revista do Colóquio, 2024)
When moving along public roads and spaces, we come across various forms of artistic expression that redesign the landscape that sticks to our eyes. We intend to discuss, based on artistic interventions, the identity mark of artists who use the language of graffiti and who occupy central areas of the capital of Espírito Santo, which would be urban voids, if it weren’t for these interventions and their ability to make us see the city for beyond the city.